Laboratory tests and game performance of young soccer players - Lipińska, Patrycja; Szwarc, Andrzej (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Results of laboratory tests could be treated as a valuable source of information about players’ physical fitness. Aim of Study. The purpose of this study was to identify laboratory physical fitness tests that could be useful for predicting competences of 17-year-old soccer players. Material and Methods. Selected components of players’ physical fitness were assessed and the effectiveness of game performance was evaluated in a group of eighteen young soccer players. The following parameters were measured: anthropometric measurements, anaerobic and aerobic capacity, locomotion speed, explosive strength of the lower limbs, reaction time, and balance. Results. The results achieved in laboratory and exercise tests were converted into ranks. An assessment of players’ effectiveness in one-on-one games was made using special one-on-one test methodology, and a list of ranked game performances was prepared. On the basis of observations made by three independent experts, the participants were classified according to their “usefulness” for the game using the Game Performance Assessment Instrument (GPAI). The ranking assessment of the effectiveness of one-on-one games and of a classified game was correlated with the results of laboratory tests. It was found that players with the highest scores in locomotion speed tests and in the explosive leg power test were also highly assessed by the experts with regard to the efficiency of their performance in one-on-one games as well as, to a slightly lesser degree, in the classified game. There was no significant relationship between the expert assessment of “usefulness” for the game and other tests. Conclusions. On the basis of strength-speed test results we may satisfactorily predict young soccer players’ efficiency of game performance
Keywords: efficiency of action; physical fitness; soccer; youth; competitive game; one-on-one game